2018
DOI: 10.1158/1055-9965.epi-18-0210
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Disparities in Time to Diagnosis and Treatment for Colorectal and Breast Cancer

Abstract: Longer cancer pathways may contribute to rural-urban survival disparities, but research in this area is lacking. We investigated time to diagnosis and treatment for rural and urban patients with colorectal or breast cancer in Victoria, Australia. Population-based surveys (2013-2014) of patients (aged ≥40, approached within 6 months of diagnosis), primary care physicians (PCPs), and specialists were collected as part of the International Cancer Benchmarking Partnership, Module 4. Six intervals were examined: pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 52 publications
4
63
1
1
Order By: Relevance
“…3,24 Additional travel burdens to cancer specialists could create barriers to the initiation and completion of guideline-indicated treatments. [25][26][27] Areas with higher rates of poverty among residents were found to have a higher likelihood of being >60 miles away from cancer care providers. This highlights the disproportionate barriers that patients with cancer who are residing in vulnerable communities face in gaining access to cancer care resources.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3,24 Additional travel burdens to cancer specialists could create barriers to the initiation and completion of guideline-indicated treatments. [25][26][27] Areas with higher rates of poverty among residents were found to have a higher likelihood of being >60 miles away from cancer care providers. This highlights the disproportionate barriers that patients with cancer who are residing in vulnerable communities face in gaining access to cancer care resources.…”
Section: Discussionmentioning
confidence: 92%
“…Weather‐associated road conditions, a lack of public transportation, and a low income level might compound the travel burden, because rural patients already experience more advanced or less treatable cancer stages . Additional travel burdens to cancer specialists could create barriers to the initiation and completion of guideline‐indicated treatments …”
Section: Discussionmentioning
confidence: 99%
“…33 A Victorian study also found that colorectal cancer patients in rural areas had significantly longer diagnostic intervals than urban patients, pointing to potential issues in timely PCP referral and diagnostic assessment. 7 In the United States, areas with reduced endoscopy capacity have less colorectal cancer screening, 34 and with density of endoscopy and cancer specialists lower in rural than urban counties, 35 access to diagnostics may be an important moderator of colorectal cancer rural-urban disparities.…”
Section: Rural-urban Pathwaysmentioning
confidence: 99%
“…There is growing evidence that prolonged colorectal and breast cancer pathways are associated with later stage disease and poorer survival, 5 and that rural patients wait longer than urban patients for diagnosis and treatment. [6][7][8] Understanding how and why longer pathways occur and whether these factors are more common in rural areas could help identify targets to reduce inequities. Furthermore, comparing pathways for cancer types with, and without, rural-urban outcome differences could provide additional insight into what may be driving disadvantage for rural patients in one group but not the other.…”
mentioning
confidence: 99%
“…This indicates that providing free CRC screening programs to the uninsured and underinsured is an efficient allocation of resources for state governments. As proposed in the literature, targeting CRC screening in rural areas could further help close the urban-rural health disparity gap [45]. The program had several advantages, including screening patients who would have normally not been screened due to lack of insurance or those who were underinsured, and therefore saving taxpayer dollars via saved future Medicaid/ Medicare expenditures or indigent care costs to the region.…”
Section: Discussionmentioning
confidence: 99%